2008
DOI: 10.1590/s0074-02762008005000006
|View full text |Cite
|
Sign up to set email alerts
|

Importance of TNF-alpha in the course of acute infection with Trypanosoma cruzi: influence of its inhibition by pentoxifylline treatment

Abstract: Infection of C3H/He mice with the Peruvian strain of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
3
7
0
2
Order By: Relevance
“…assessed the participation of TNF-α on cellular necrosis and destruction of infected macrophages in the spleen of mice during the acute phase of T. cruzi infection, they observed the expression of this cytokine in necrotic areas within the germinal center and in the red pulp, suggesting a role for TNF-α in the exacerbation of tissue damage. This same result was also observed recently by Andrade et al (2008) [33]. Furthermore, kinetic investigations on the activation of macrophages during Chagas disease, demonstrated that macrophages of mice susceptible to infection produce higher levels of TNF-α than macrophages from resistant mice strains [34] [35].…”
Section: Discussionsupporting
confidence: 88%
“…assessed the participation of TNF-α on cellular necrosis and destruction of infected macrophages in the spleen of mice during the acute phase of T. cruzi infection, they observed the expression of this cytokine in necrotic areas within the germinal center and in the red pulp, suggesting a role for TNF-α in the exacerbation of tissue damage. This same result was also observed recently by Andrade et al (2008) [33]. Furthermore, kinetic investigations on the activation of macrophages during Chagas disease, demonstrated that macrophages of mice susceptible to infection produce higher levels of TNF-α than macrophages from resistant mice strains [34] [35].…”
Section: Discussionsupporting
confidence: 88%
“…During acute T . cruzi infection, PTX administration reduced the number of TNF + cells in necrotic areas in the spleen [ 41 ]. Thus, a reduction in TNF expression was expected in our models of CCC subjected to PTX treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, TNF-α blockade has been shown to decrease necrotic areas in the spleen during acute T. cruzi infection (Andrade et al 2008). Conversely, treatment with Etanercept (soluble human TNFR2/p75 that binds TNF-α and lymphotoxin α) aggravated chronic chagasic cardiomyopathy in hamsters, leading to the claim that the absence of TNF-α signaling may be deleterious to the failing heart in Chagas disease cardiomyopathy (Bilate et al 2007).…”
Section: Discussionmentioning
confidence: 99%